Teacher Targets: A model for CLIL and ELF teacher education in polytechnic settings - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Carmen Sancho Guinda Universidad Politécnica de Madrid, Spain   ABSTRACT The objective of this paper is to present an alternative model for CLIL/ELF teacher education, called the Teacher Target Model, which may help hard-science teachers undertake English-medium instruction more efficiently. Conceived as a visual educational trope for changing mentalities and practices, it derives from the needs analysis of a group of polytechnic teachers who have participated in the cycles of in-service training seminars given at the Polytechnic University of Madrid since 2009. Their notions, impressions, and video-recorded performances reveal that in general they hold a monolithic conception of classroom interactions and teaching procedures, with an ensuing impoverishment of genre and language repertoires. To bridge this gap, the model proposed here cross-weaves five discursive strands converging in university lectures, namely disciplinary discourse, (meta)discourse of the medium, embedded genres, lecture phase, and teaching style, thus fostering natural communication beyond the delivery of technical content and bringing ELF instruction closer to the CLIL dynamics.